Analisis Semantik atas Terma Proses Penciptaan Manusia dalam Al-Qur'an - Khakim, Lukman; Mohammad Rofiqi; Lilik Rochmad Nurcholisho (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The study of humans is always interesting to discuss because by knowing how he came from and he will end, he will know the meaning or purpose of living life. This research focuses on human creation by using semantics to reveal the meaning contained in the Qur'an which specifically discusses the process of human creation. This research uses a qualitative method. Where researchers collect data and analyze it then describe it descriptively. This research seeks to prove that the Qur'an is the main reference for humans because its contents remain compatible with the science that has developed to date and will continue to do so.